Contextual Distinctiveness Affects the Memory Advantage for Vocal Melodies. Issue 1 (3rd April 2019) - Weiss, Michael W.; Schellenberg, E. Glenn; Peng, Chen; Trehub, Sandra E.
ABSTRACT: Memory is affected by stimulus salience. For example, vocal melodies are remembered better than instrumental melodies, presumably because of their status as biologically significant signals. We asked whether the memorability of inherently salient vocal melodies is affected by local factors such as contextual distinctiveness. In Experiments 1A and 1B, three conditions differed in the prevalence of vocal renditions (sung to la la ) relative to piano renditions– 25%, 50%, or 75%. After asingle exposure to 24 unfamiliar folk melodies, listeners rated their confidence that each of 48 melodies (half heard previously) was old or new. In Experiment 2, contextual distinctiveness was manipulated by blocking melodies (half vocal, half piano) by timbre during exposure with mixed timbres at test, or timbres mixed at exposure and blocked at test. In Experiments 1A and 1B, the memory advantage for vocal melodies was largest when the melody set was 25% vocal, smaller but still evident when 50% vocal, and absent when 75% vocal, even with three different vocalists. In Experiment 2, both conditions yielded a similar voice advantage. The results replicated the recognition advantage for vocal melodies and revealed that contextual distinctiveness involving the prevalence of vocal melodies influenced this advantage but blocking by timbre did not.